Deiksis Ruang dan Waktu pada Film Stand by Me Doraemon 2 Karya Takashi Yamazaki - Rahayu, Ajeng Agustina; Utari, Retno (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
In communicating, pointing words or deixis are often used when talking to the interlocutor, especially in Japanese movies. For this reason, this study aims to identify the types of space and time deixis and find out the types of references contained in the Stand by Me Doraemon 2 movie by Takashi Yamazaki. The methodology of this qualitative study is descriptive analysis which analyzed the conversation between characters consisting deixis space and time words in Japanese movie titled Stand by Me Doraemon 2. The data were collected using the listening and note taking method. Then they were analyzed by Miles and Huberman method, which the important data is reduced, grouped, and summarized according to the research focus. The results showed that in Stand by Me Doraemon 2 there was deixis of space and time. There were 28 deixis of space including space, place, state and direction and 18 deixis of time including final, present, and future time. It is found that the most frequently used deixis of space was これ (kore) which means “this”. On the other hand, the most frequently deixis of time was さっき (sakki) which means “just know”. Overall, there were 19 types of endophoric references and 27 types of exophoric references. This research is expected to be used as learning material for Japanese language teachers and learners.